x(x-6)=40

Apply the distributive property.

x⋅x+x⋅-6=40

Simplify the expression.

Multiply x by x.

x2+x⋅-6=40

Move -6 to the left of x.

x2-6x=40

x2-6x=40

x2-6x=40

Move 40 to the left side of the equation by subtracting it from both sides.

x2-6x-40=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -40 and whose sum is -6.

-10,4

Write the factored form using these integers.

(x-10)(x+4)=0

(x-10)(x+4)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-10=0

x+4=0

Set the first factor equal to 0.

x-10=0

Add 10 to both sides of the equation.

x=10

x=10

Set the next factor equal to 0.

x+4=0

Subtract 4 from both sides of the equation.

x=-4

x=-4

The final solution is all the values that make (x-10)(x+4)=0 true.

x=10,-4

Solve using the Square Root Property x(x-6)=40